Development of High-Fidelity Numerical Methodology for Prediction of Vehicle Interior Noise Due to External Flow Disturbances Using LES and Vibroacoustic Techniques - Songjune Lee; Sang-heon Lee; Cheolung Cheong (Applied Sciences, 2022)
A pleasant and quiet cabin in driving a car is one of the most critical factors affecting a customer’s choice in a market. As the traditional noise sources such as power trains become less, the relative contribution of aerodynamic noise to the interior noise of a road vehicle becomes even more critical. In this study, a high-fidelity numerical methodology is developed for the reliable prediction and analysis of the interior transmitted noise due to external flow disturbance. The developed numerical methodology is based on the sequential application of the high-resolution LES technique, wavenumber–frequency transform, and vibroacoustic model. First, the compressible LES techniques with high-resolution grids are employed to accurately predict the external turbulent flow and aeroacoustic fields due to the turbulent flow, at the same time, of a vehicle running at a speed of 110 km/h. Second, surface pressure fluctuations on the front windshield and side windows, obtained from the LES simulation, are decomposed into incompressible and compressible ones using the wavenumber–frequency transform. Lastly, the interior sound pressure levels are predicted using the vibroacoustic model, which consists of the finite element (FE) and statistical energy analysis (SEA) methods. For the efficient computation of the vibroacoustic interaction between the vibration of the vehicle windows and the acoustic field inside the cabin room, the FE and SEA methods are applied in low- and high-frequency ranges, respectively. The predicted interior sound pressure spectral levels agree well with the measured ones. In addition, although the magnitudes of the compressible pressure components are generally lower than those of the incompressible ones, the compressible field is found to contribute more to the interior noise in high-frequency bands. The physical mechanism of the higher transmission is shown to be related to the coincident effect between the compressible pressure field and the structural vibration of the vehicle window.